Growth of Brachiaria brizantha planted at different densities and seasons in Santa Fé system with a culture of soybean - Erasmo, Eduardo A L; Gonçalves, Rogério C; Mata, Jhansley F Da; Oliveira, Vinícius A; Benício, Luíz P F (Emirates Journal of Food and Agriculture, 2017)
This study aims to evaluate the density and planting period of the grass Brachiaria brizantha in consortium with the soybean. The study was conducted under field conditions at the experimental station of University of Tocantins. The experimental design used was a randomized block design, in factorial scheme of (2 x 5) + 4, with four repetitions, including both sowing of Brachiaria brizantha (20 and 30 days after the emergence – DAE, of soybeans), five Brachiaria seeding densities (0, 3, 6, 9, and 12kg of seed ha-1) and Brachiaria grown individually in the four densities tested, constituting itself as witness reference. To assess the growth of the Brachiaria, the plants contained in an area of ​​(0.33 x 0.40m) to 140 DAP of soy were collected in each plot, determining the number of tillers per plant; height and dry weight of shoots; leaf dry mass and dry mass stalk. Data were submitted to regression analysis. The cultivation of Brachiaria intercropped with soybean provoked a decrease in all parameters evaluated. The increase in the density of sowing promoted a reduction in the tillering and an increase in dry matter production and height of the plant.